Quando penso em mim, penso no CAPS: o cuidado de si frente às vivências de profissionais da saúde mental - Mercom, Luciana Nascimento (2020)
The mental health professional is at the center of the Brazilian Psychiatric Reform, a movement that broadens the look upon madness, brings new ways of working and a series of debates and challenges. As a substitute device for psychiatric hospitals, the P